2013
DOI: 10.4103/0976-9668.117010
|View full text |Cite
|
Sign up to set email alerts
|

Dental health status and treatment needs of transport workers of a northern Indian city: A cross-sectional study

Abstract: Aim:To assess the dental health status and treatment needs of transport workers working in Chandigarh Transport Undertaking (C.T.U.) buses, Chandigarh.Materials and Methods:A cross-sectional study was conducted on all the available C.T.U. workers at all three bus depots. The data were recorded on a modified W.H.O. format (1997). A total of 1008 subjects constituted the final sample size.Results:The mean age of the subjects was 45.3 ± 7.8 years, and 97% (978) were males. Prevalence of dental caries was 63.4% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
(18 reference statements)
2
9
3
Order By: Relevance
“…In this study, it was found that the majority of workers had up to 11 years of schooling, corroborating previous findings [8]. In addition to the fact that education is related to the actions of people as citizens, it also influences their income, which becomes an agent of great influence on individuals' lives [16].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In this study, it was found that the majority of workers had up to 11 years of schooling, corroborating previous findings [8]. In addition to the fact that education is related to the actions of people as citizens, it also influences their income, which becomes an agent of great influence on individuals' lives [16].…”
Section: Discussionsupporting
confidence: 75%
“…Thus, epidemiological surveys aimed at assessing the working population have shown predominance of male workers [8,12,15], opposing to data obtained in this study that found a greater number of women. It is assumed that such divergence occurred as a consequence of the insertion of these workers into a textile industry in which individuals perform cutting and sewing activities, which is culturally designated to females.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Third, the values of the decayed, missing, and filled teeth (DMFT) index for different age groups in marble mine laborers (3.13) [2] or transport workers (5.02) [3] are higher than reported in this article (2.89). Even the age-specific highest value reported in this article (3.59 for the 37–46 year age group) is lower than that reported for marble mine workers (4.0 seen in the 45–54 year age group).…”
contrasting
confidence: 57%